STRATEGI PENINGKATAN KOMPETENSI GURU SEKOLAH DASAR MELALUI PELATIHAN PEMBELAJARAN BERBASIS KARAKTER KEARIFAN LOKAL - La Ode Monto Bauto; I Ketut Suardika; Sulsalman Moita; Amiruddin Amiruddin; Aryuni Salpiana Jabar (Universitas Halu Oleo, 2022)
The objectives of the Internal Community Partnership Program are: (1) Improving the competence of teachers in understanding, mastering and practicing character-based learning of local wisdom, through: introduction to local languages, traditional games, traditional arts, customs, and so on; (2) Strengthening mutual relations between teachers and students in the learning process and in everyday life as a manifestation of social competence and personality competence; (3) Increasing the existence of teacher deliberation forums for subjects based on learning the character of local wisdom; (4) Produce students who not only have intellectual intelligence, but have affective intelligence derived from ethics, good morals, honesty, discipline that can be obtained from the values of local wisdom. To achieve this goal, the method carried out is training by focusing on socialization and FGD approaches. The socialization and FGD approach emphasizes the strategy of partnership and synergy between teachers by strengthening the forum for teacher deliberation on local content subjects. The results of the Internal Community Partnership Program show that: (1). Training to Improve the Competence of Elementary School Teachers through Character-Based Learning Local Wisdom is a vehicle for teachers to understand, master, and implement it in a learning process synergized with traditional cultural values such as: traditional arts, traditional games, traditional knowledge, and so on; (2) Training on Improving the Competence of Elementary School Teachers through Character-Based Learning Local Wisdom can improve professional competence, pedagogic competence, personality competence, and teacher social competence to encourage students to understand knowledge in the cognitive, psychomotor, and affective realms.